Biocidal effect of castor (Ricinus communis) seed extract on Ulomoides dermestoides (Coleoptera: Tenebrionidae) - de la Cruz – Leytón, Camila (2023)
Ulomoides dermestoides Fairmaire, 1893 (Coleoptera: Tenebrionidae), is a pest of stored grains, aff ecting the germination and commercial value of the seeds. Ricinus communis (Linneo, 1753) (Euphorbiaceae) has compounds with phytotoxic properties such as ricinin (toxic alkaloid), and, ricin (phytotoxic albumin). Th is research aims to evaluate the biocidal eff ect of R. communis essential oil extracted by maceration and Soxhlet methods on larvae of the last stages and adults of U. dermestoides. Th e experimental design consisted of a control group (C) and three experimental groups E1 (33%), E2 (60%), and E3 (70.4%), with four repetitions per treatment. Th e evaluation period was 120 hours in 24-hour intervals. Th e results obtained indicate that treatments E2 and E3 have the greatest biocidal eff ect on larvae and adults of U. dermestoides, recording the highest number of dead individuals within 24 hours of the start of the treatment. We conclude that the essential oil of R. communis obtained by the maceration and Soxhlet method has a biocidal eff ect on larvae of the last stages and adults of U. dermestoides.